Institutional Actions Against COVID-19: An Analysis of Mexican Autonomous Public Universities' Websites - Shamaly Alhelí Niño Carrasco; Juan Carlos Castellanos Ramírez; Rubén Bermúdez Vivas (Universidad Autónoma de Baja California, 2022)
The objective of this research was to identify and characterize actions taken by autonomous public universities in Mexico in response to COVID-19. The study is theoretically grounded in the notion of emergency education, which refers to broad prevention, mitigation, preparation, response, normalization, and educational recovery mechanisms for disasters. We conducted an exploratory-descriptive study, analyzing information posted on university websites from January 15 to June 30, 2020. It was found that many universities adopted reactive measures, albeit with no far-reaching prevention and mitigation strategies before they went into shutdown. We conclude there is a need to develop institutional policies that lay the foundation for an educational culture able to respond proactively to future catastrophes and for a shift from enacting guidelines for academic continuity to preparing broad education programs for emergencies.